Hawkeye. Family reunion - Thompson, Kelly, 1976- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2018)
"Can Los Angeles really handle two Hawkeyes? Just as Kate Bishop reaches out to ask for Clint Barton's help with finding her dead mother, the senior bowman shows up needing help of his own. An unknown party is gunning for him - and their attack kicks off a wild chase across the City of Angels! Now, Hawkeye and Hawkeye must try their hardest to stay one step ahead, fully alive, and with minimal property damage...well, okay, with moderate property damage. But who has Clint and Kate in their sights, and what is their sinister agenda? The Hawkeyes are reunited and it feels so good!"--Amazon.